Induction informational, informational use, the behavior of the product and user information. - سلمان عامر محمد; سلمان وفاء حسين (Journal of Economics and Administrative Sciences, 2016)
Abstract: This study seeks to shed light on the important processes are linked to the impact of accounting information on the behavior of producer and user of information and are urging informational and informational use. That accounting as a system of accounting information and functions of the delivery of information to decision makers Under behavioral entrance to the formulation of accounting theory should be taken into account Othertlk accounting information in the behavior of the decision maker which requires an explanation of human behavior and predictable. On the other hand that the accounting information that should be delivered to the decision maker will affect your behavior accountant and that’s what he referred to Prakash, describing the process of induction informational and hence the person will be affected by his conduct accounting information once as a transmitter of information (the accountant) and once as a user of the Information (receiver), and know first informational induction process and the second process informational use. That all of the product and the user information his behavior after the informational content to the process of financial reporting and this has been proved by the study through a questionnaire that was distributed to a sample of companies listed in the Iraqi Stock Exchange companies and using a number of statistical methods, and reached a number of conclusions most important that user behavior has to do with the nature and type of information that he had received and which are reflected on the type of decisions, whether investment decisions, credit and other decisions, and the sender information (the accountant) and is required to deliver information to the recipient, his behavior is influenced by a reversal Reflction user behavior information through its decisions and this the so-search information as mentioned either the most important recommendations of the study are that the accountant familiar with the needs of accounting information and orientation so that users use the methods of accounting methods that generate accounting information in line with the orientations and behavioral decision-maker ..